1997
DOI: 10.1016/s0304-3959(97)00028-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological classification of central post-stroke pain: comparison with the results of chronic motor cortex stimulation therapy

Abstract: In an attempt to clarify the neurochemical background of central post-stroke pain and to undertake a pharmacological analysis, the basic pharmacological characteristics of this intractable pain syndrome were investigated by the morphine, thiamylal and ketamine tests. In addition, the correlation between the pharmacological characteristics and the effects of chronic motor cortex stimulation therapy was examined. The study employed 39 central post-stroke pain patients who had intractable hemibody pain associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 57 publications
0
106
0
4
Order By: Relevance
“…For example, several investigators 24,50 have suggested that specific neurological subgroups of neuropathic pains may respond to opioids. Thus, it is possible that 'opioid responsive' neuropathic pain subgroups may also exist in the SCI chronic pain population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several investigators 24,50 have suggested that specific neurological subgroups of neuropathic pains may respond to opioids. Thus, it is possible that 'opioid responsive' neuropathic pain subgroups may also exist in the SCI chronic pain population.…”
Section: Discussionmentioning
confidence: 99%
“…Barbiturate sensitivity and opioid insensitivity have been suggested as possible predictors of response. 1,22,24 Transcranial magnetic stimulation may be another useful predictor of response.1,14 Another possible predictor in patients with poststroke pain could be the level of muscle strength demonstrated in the painful area.10 Results of such preoperative testing, however, are no guarantee of a successful outcome, as not all patients who respond to propofol respond to MCS and, equally, morphine-insensitive patients have been shown to respond to stimulation. 1 We have not, therefore, routinely performed any specific investigations other than head computerized tomography and magnetic resonance imaging, preoperative chest radiography, electrocardiography and blood count, clotting screen, and serum chemistry.…”
mentioning
confidence: 99%
“…Therefore, both hand and foot areas were stimulated together, since it is important to induce muscle contraction or muscle twitch in the painful area for the motor cortex stimulation therapy. 10,[19][20][21][22] Our previous experience with patients with MMT of 4 suggested that the threshold intensity to induce muscle contraction under stimulation conditions of 25 Hz with 0.2 msec duration is 5.8 ± 0.9 V (n = 10). In the present patients, muscle contraction was induced at 2.9 V in Case 1 and 3.3 V in Case 2.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]7,8,[11][12][13]16,17,22) In the large series, the long-term success rate for pain alleviation was about 50%. The pain control provided by motor cortex depends on stimulation of neuronal circuits mediated by corticospinal tract neurons originating from the motor cortex.…”
Section: Introductionmentioning
confidence: 99%